Kairo, Ägypten: Sichtung, Katalogisierung und Verglasug der Michigan Papyri im Ägyptischen Museum - Römer, Cornelia (e-Forschungsberichte des DAI, 2023)
The aim of the project is to study and to publish a group of papyri from theancient town of Karanis in the Fayum, now kept in the Egyptian Museum,Cairo. A first volume with 32 texts was published in 2014; with this volume,Part 1 of the Project has been successfully concluded. P. Mich. contains literaryas well as documentary texts which shed new light on life in Karanis in the2nd century CE. There are fragments of Homer’s Iliad, a medical handbook,and a list of titles of satyr-plays and comedies; among the documents is acomplaint about robbery, lists of people’s names who payed their taxes, anda letter written by a woman.